2021
DOI: 10.30880/ijie.2021.13.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Carbon Sequestration of Green Roof Plants in Tropical Climate

Abstract: A green roofs is one of the recommended methods of practice in improving the sustainability of urban areas. Green roofs can be used as a passive technique to reduce carbon dioxide (CO2) emissions from the atmosphere. This is due to the role of green roof layers which are vegetation and soil to process the photosynthesis activities and to capture CO2 from the atmosphere. The objective of this paper is to quantify and to compare the amount of CO2 sequestration by ten potential green roof plants, in order to esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A study by Llodrà-Llabrés and Cariñanos (2022) indicates that urban green areas have significant potential for pollinators' conservation by adding species that bloom throughout the year and not only in the main flowering season to maintain the continuous supply of floral resources. Another study by Yacob et al (2021) related to quantifying and comparing the amount of carbon sequestered by ten different plants for a tropical climate revealed that a perennial species has the highest photosynthesis or carbon sequestration rates compared to the other nine. All these factors are important to be considered while planning strategic planting.…”
Section: Key Strategies For Carbon Sequestration and Habitat Provisio...mentioning
confidence: 99%
“…A study by Llodrà-Llabrés and Cariñanos (2022) indicates that urban green areas have significant potential for pollinators' conservation by adding species that bloom throughout the year and not only in the main flowering season to maintain the continuous supply of floral resources. Another study by Yacob et al (2021) related to quantifying and comparing the amount of carbon sequestered by ten different plants for a tropical climate revealed that a perennial species has the highest photosynthesis or carbon sequestration rates compared to the other nine. All these factors are important to be considered while planning strategic planting.…”
Section: Key Strategies For Carbon Sequestration and Habitat Provisio...mentioning
confidence: 99%